Model-Model Kebersamaan Iman Orang Muda Katolik: Menjawab Tantangan di Masa Kini - Septa Karunia, Vinsensius; Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2025)
Amidst an increasingly modern era, Catholic youth face challenges in building a solid and relevant faith-based community. The methods employed in this study include a review of Church documents, especially Christus Vivit and Young People, the Faith, and Vocational Discernment, thematic-qualitative analysis, and correlation. The qualitative analysis in this research was based on the survey data distributed to limited respondents. Based on these observations, the study proposes four models of faith fellowship: the Missionary Friendship Model, the Youthful Spirit Model, the Joyful Faith Dialogue Model, and the Second Home Model. Each model is analyzed in terms of its biblical imagery, Church teaching foundations, theological reflection, implications and contextualization, as well as corrective imagery. This research shows that faith fellowship rooted in Christ, built up through communicative relationships, and firm in both personal and communal witness, can provide a meaningful response to the needs of Catholic youth today. These models are expected to inspire Catholic youth, their mentors, and the local Church to nurture a vibrant, inclusive, and missionary faith community.